Media Komunitas dan Media Literacy - ., Pawito (FISIP Universitas Atma Jaya Yogyakarta, 2007)
Abstract:This essay deals with community media in relation to media literacy. After a short discussion on a number of community media characters is made the essay goes further with somewhat detail theoretical presumptions of the roles of media community with respect primarily to the development as Amartya Sen mentioned about. The author suggests that community media may play some significant roles in the development including (a) disseminating information (from varieties of perspective), (b) facilitating public discussion, (c) helping to reach solutions of problems, (d) encouraging participations, and (e) encouraging the development of media literacy. Regarding the last point the author remarks that media community may have a dual-roles i.e facilitating community’s member in media participation and facilitating community’s member in media education.